Perception of facial expressions reveals selective affect-biased attention in humans and orangutans - Carla Pritsch (Nature Portfolio, 2017)
Abstract Rapid detection and recognition of another individual’s emotional state plays a pivotal role for humans and, most likely, other social species. Proper reactions contribute to an individual’s survival in potentially dangerous situations; this is ensured by a preferential attention towards salient cues. The predisposition to attend to certain categories of affectively salient stimuli– also referred to as affect-biased attention - is likely shared with other species, since fast detection of and appropriate reaction to threats is crucial to survival. We compared human children and one of our close relatives, Sumatran orangutans (Pongo abelii), and predicted that both look more attentively and longer at emotionally salient facial expressions of their own and corresponding other species, compared to neutral faces. However, in contrast to a bias towards emotions providing relevant information by indicating a threat, both species preferentially looked at the fear-related, but not the angry faces of humans and consistently preferred the silent-bared teeth espressions in orangutans. The differential attention towards certain expressions might derive from their social function and the need to detect a potential threat in the environment. Our findings are consistent with claims rooting this affect-biased attention characteristic of human perception in our evolutionary history.